2008
DOI: 10.1128/aem.01058-07
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan Modification in Aspergillus Species

Abstract: The production by filamentous fungi of therapeutic glycoproteins intended for use in mammals is held back by the inherent difference in protein N-glycosylation and by the inability of the fungal cell to modify proteins with mammalian glycosylation structures. Here, we report protein N-glycan engineering in two Aspergillus species. We functionally expressed in the fungal hosts heterologous chimeric fusion proteins containing different localization peptides and catalytic domains. This strategy allowed the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…After the N-glycosidase treatment, the apparent molecular masses of WscA-HA and WscB-HA decreased to 43 to 48 kDa and 48 to 63 kDa, respectively. The size differences before and after N-glycosidase treatment were consistent with the existence of three N-glycosylation sites with the typical N-glycan structure [Man (5)(6)(7)(8)(9)(10)(11)(12) GlcNAc 2 ] that has been described for Aspergillus glycoproteins (1,19,49,50). Thus, our results suggest that both WscA and WscB are N-glycosylated in A. nidulans.…”
supporting
confidence: 74%
“…After the N-glycosidase treatment, the apparent molecular masses of WscA-HA and WscB-HA decreased to 43 to 48 kDa and 48 to 63 kDa, respectively. The size differences before and after N-glycosidase treatment were consistent with the existence of three N-glycosylation sites with the typical N-glycan structure [Man (5)(6)(7)(8)(9)(10)(11)(12) GlcNAc 2 ] that has been described for Aspergillus glycoproteins (1,19,49,50). Thus, our results suggest that both WscA and WscB are N-glycosylated in A. nidulans.…”
supporting
confidence: 74%
“…By comparing the experimental masses of CBHI with the theoretical ones, the additional peak with m/z 2639.2 cumulatively differed from the peak with m/z 1500.8 by 1138 Da. According to the molecular weight of the N-glycan structure detected using MALDI-TOF (20), it was found that (Man) 3 (GlcNAc) 2 ϩ GlcNAc bound to the Asn-137 of CBHI-A. Similar analyses of the MS data were performed for the other CBHI glycoforms.…”
Section: Identification Of Four Purified P Decumbens Proteins Via Mamentioning
confidence: 81%
“…By comparing the experimental masses of glycopeptides with the theoretical ones, more masses were found. The molecular weights of the glycans detected using MALDI-TOF (20) were acquired from a previous paper and used to analyze the N-glycan structures of the different CBHI glycoforms.…”
Section: Identification Of Four Purified P Decumbens Proteins Via Mamentioning
confidence: 99%
“…The gpdA promoter is expressed efficiently in A. niger strains [7,17]. The construction of pANJil included a DNA sequence encoding the first 26 amino acids of the xlnD signal peptide (ALA-QA), according to Bendtsen et al [3].…”
Section: Resultsmentioning
confidence: 99%